2009
DOI: 10.1038/ejhg.2009.73
|View full text |Cite
|
Sign up to set email alerts
|

A novel double deletion underscores the importance of characterizing end points of the CFTR large rearrangements

Abstract: Large genomic rearrangements in patients with cystic fibrosis (CF) account for up to 16 -24% of CF alleles negative for point mutations in European populations. Herein, we identified a new large rearrangement removing exon 19 in a young CF patient, who hitherto harbored only the F508del mutation. By using LightCycler technology, we successfully and rapidly delineated the deletion end points by determining the relative copy number of a set CFTR sequence from introns 18 to 19. Fine mapping of the sequences borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…We next used a previously developing and practical technique to determine the endpoints using quantitative PCR technology (Taulan et al, 2009). With reductions in gene copy number, from two to one, more readily identifiable, we successfully revealed this duplication using our previously developed and practiced quantitative PCR technology (Taulan et al, 2009), followed by direct DNA sequencing to precisely map the duplication breakpoint junctions Such precise mapping is widely accepted as indispensable for both diagnostic and global understanding of the large rearrangements identified at the CFTR locus. Majority of deletions/duplications can be classified as severe mutations as associated with severe phenotype.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We next used a previously developing and practical technique to determine the endpoints using quantitative PCR technology (Taulan et al, 2009). With reductions in gene copy number, from two to one, more readily identifiable, we successfully revealed this duplication using our previously developed and practiced quantitative PCR technology (Taulan et al, 2009), followed by direct DNA sequencing to precisely map the duplication breakpoint junctions Such precise mapping is widely accepted as indispensable for both diagnostic and global understanding of the large rearrangements identified at the CFTR locus. Majority of deletions/duplications can be classified as severe mutations as associated with severe phenotype.…”
Section: Resultsmentioning
confidence: 98%
“…Informed consent to CFTR studies has been previously obtained from parents at time of referral. A SQF-PCR assay was used to detect large rearrangements in the CFTR gene as previously reported (primers on demand) (Taulan et al, 2009). The method relies on the comparison of the fluorescent profiles of multiplex PCR fragments obtained from different samples, the amplification being stopped at the exponential phase.…”
Section: Cf Patient and Identification Of Gross Rearrangement By Semimentioning
confidence: 99%
See 2 more Smart Citations
“…This sequence includes the 'immunoglobulin heavy chain class switch repeat', a short direct repeat of 5 bp [CCCCA] [Chen et al, 2005a, b], which has been reported to mediate slippage mispairing and to cause deletions and translocations [Demura et al, 2002;Abeysinghe et al 2003]. It is well documented that the slippage mechanism during replication process is mediated by the presence of direct repeats (2-8 bp) at the end points of deletions/duplications and that only one short repeat is retained in the rearrangement [Ketterling et al, 1994;Chen et al, 2005a, b;Taulan et al, 2009]. Several characterized deletions showed locus variability both in the sequence and length of the direct repeats.…”
Section: Discussionmentioning
confidence: 99%